2016
DOI: 10.1186/s12936-016-1283-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic properties of intramuscular versus oral syrup paracetamol in Plasmodium falciparum malaria

Abstract: BackgroundFever is an inherent symptom of malaria in both adults and children. Paracetamol (acetaminophen) is the recommended antipyretic as it is inexpensive, widely available and has a good safety profile, but patients may not be able to take the oral drug reliably. A comparison between the pharmacokinetics of oral syrup and intramuscular paracetamol given to patients with acute falciparum malaria and high body temperature was performed.MethodsA randomized, open-label, two-treatment, crossover, pharmacokinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Paracetamol (acetaminophen) is the recommended antipyretic therapy as it is safe, inexpensive, and widely available. 33 However, paracetamol has been associated with a prolonged parasite clearance time, which our study suggests could be, to some extent, explained by increased survival in normothermia. 5 A more recent randomized controlled trial did not show a difference in parasite clearance between patients treated with or without paracetamol.…”
Section: Discussionmentioning
confidence: 60%
“…Paracetamol (acetaminophen) is the recommended antipyretic therapy as it is safe, inexpensive, and widely available. 33 However, paracetamol has been associated with a prolonged parasite clearance time, which our study suggests could be, to some extent, explained by increased survival in normothermia. 5 A more recent randomized controlled trial did not show a difference in parasite clearance between patients treated with or without paracetamol.…”
Section: Discussionmentioning
confidence: 60%
“…A study which compared the pharmacokinetics of oral paracetamol versus intramuscular paracetamol given to patients with acute falciparum malaria with high fever revealed that both methods were able to achieve mean steady state therapeutic drug levels in serum. 14 During the dengue fever season, the physician must avoid unnecessary intramuscular injections in managing febrile episodes. Unnecessary intramuscular injections can be associated with local complications such as pain swelling or abscess formation.…”
Section: Discussionmentioning
confidence: 99%
“…This work, in conjunction with the latest reports on the mechanism of action of Paracetamol, trying to point out that it is not a panacea devoid of side effects, and indeed, especially when is taken regularly and in large doses (> 4 g/day), there is a risk of serious side effects [7].…”
Section: Antipyretic Syrupmentioning
confidence: 95%